Peran Polres Pegunungan Bintang Sebagai Mediator Konflik - Italy, Hermanus (CENDERAWASIH: Jurnal Antropologi Papua, 2023)
The aim of this research is to analyze conflicts that occur, including the sources of conflict in the working area of the Pegunungan Bintang Police, Papua Regional Police, in the mediation process by the police as community partners. The approach used in this research is the sociological juridical method. Data sources come from observations, interviews and literature studies. The results of the research show that the conflict that occurred in the Pegunungan Bintang Police area was related to information transparency and resource support. The first conflict was related to the commotion that occurred during the GIDI men's and women's volleyball final in the Bintang Mountains Regency. The National Police, through the Integrated Police Service Center (SPKT) at the Bintang Mountains Police, Papua Regional Police, mediates the report. Second, conflict related to services at Oksibil Regional Hospital with the people of the District Pegunungan Bintang. This conflict was triggered by a lack of medicines provided by the hospital to provide health services.